Study of the adsorption of dyes employed in the food industry by activated carbon based on residual forestry - Valladares C. (2019)
An activated carbon (adsorbent) was prepared from a forestry residual biomass (Capparis scabrida sawdust) by chemical activation with ZnCl2. The adsorbent was tested in kinetic experiments to remove three anionic dyes widely used in the food industry: tartrazine (TR), brilliant scarlet 4R (BS4R) and brilliant blue (BB). The adsorbent was able to remove the dyes in different intensities, and the revealed order of their adsorption ability was BS4R>TR>BB. Most of the kinetic data fit best to the pseudo-second order model; however, high accordance with other models indicates that there is more than one phenomenon to explain the adsorption process. Analyzing the data that fit well to the pseudo-second order model and considering that the equilibrium was reached, the equilibrium adsorption capacity (qe) for TR was 55.3 mg/g (when the AC load was 1 g/l and the TR initial concentration was 50 mg/l); for BS4R, 72.1 mg/g (when the AC load was 1 g/l and the TR initial concentration was 50 mg/l); and for BB, 14.1 mg/g (when the AC load was 1 g/l and the TR initial concentration was 10 mg/l) as the maximum values. AC based on Capparis scabrida residual biomass is a promising material for use in the purification of water polluted by anionic azo dyes.